Chứng minh biểu thức dưới đây không phụ thuộc vào biến: (x-1)^3 + (x+1)^3 + 6(x+1)(x – 1) (x-3)(x+3)(x^2 + 9) – (x^2 – 2)(x^2 -2) (3x+1)^2 – 2(3x + 1)

Question

Chứng minh biểu thức dưới đây không phụ thuộc vào biến:
(x-1)^3 + (x+1)^3 + 6(x+1)(x – 1)
(x-3)(x+3)(x^2 + 9) – (x^2 – 2)(x^2 -2)
(3x+1)^2 – 2(3x + 1)(3x – 5)+(3x- 5)^2
Cảm ơn!

in progress 0
Lyla 3 tuần 2021-08-21T16:34:38+00:00 1 Answers 2 views 0

Answers ( )

    0
    2021-08-21T16:35:40+00:00

    Giải thích các bước giải:

     $1)
    (x-1)^3-(x+1)^3+6(x+1)(x-1)\\
    =x^3-3x^2+3x-1-(x^3+3x^2+3x+1)+6(x^2-1)\\
    =x^3-3x^2+3x-1-x^3-3x^2-3x-1+6x^2-6\\
    =(x^3-x^3)+(-3x^2-3x^2+6x^2)+(3x-3x)+(-1-1-6)\\
    =-8\\
    2)
    (x-3)(x+3)(x^2+9)-(x^2+2)(x^2-2)\\
    =(x^2-9)(x^2+9)-(x^4-4)\\
    =x^4-81-x^4+4\\
    =-77\\
    3)
    (3x+1)^2-2(3x+1)(3x-5)+(3x-5)^2\\
    =\left [3x+1-(3x-5)  \right ]^2\\
    =\left [3x+1-3x+5  \right ]^2\\
    =6^2=36$

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )